Convergence of cloud with AI for big data analytics foundations and innovation - Rawat, Danda B. 1977-; Awasthi, Lalit Kumar; Balas, Valentina Emilia; Kumar, Mohit; Samriya, Jitendra Kumar (Wiley, 2023)
This book covers the foundations and applications of cloud computing, AI, and Big Data and analyses their convergence for improved development and services. The 17 chapters of the book masterfully and comprehensively cover the intertwining concepts of artificial intelligence, cloud computing, and big data, all of which have recently emerged as the next-generation paradigms. There has been rigorous growth in their applications and the hybrid blend of AI Cloud and IoT (Ambient-intelligence technology) also relies on input from wireless devices. Despite the multitude of applications and advancements, there are still some limitations and challenges to overcome, such as security, latency, energy consumption, service allocation, healthcare services, network lifetime, etc. Convergence of Cloud with AI for Big Data Analytics: Foundations and Innovation details all these technologies and how they are related to state-of-the-art applications, and provides a comprehensive overview for readers interested in advanced technologies, identifying the challenges, proposed solutions, as well as how to enhance the framework. Audience Researchers and post-graduate students in computing as well as engineers and practitioners in software engineering, electrical engineers, data analysts, and cyber security professionals.
Includes bibliographical references and index. - Online resource; title from PDF title page (John Wiley, viewed February 15, 2023)
Keywords: Cloud computing; Artificial intelligence; Big data; Infonuagique; Intelligence artificielle; Données volumineuses; artificial intelligence